A peptide coating preventing the attachment of Porphyromonas gingivalis on the surfaces of dental implants. (24th February 2020) - Fang, Dongdong; Yuran, Sivan; Reches, Meital; Catunda, Raisa; Levin, Liran; Febbraio, Maria
Abstract: Objectives: The aim of this study was to investigate whether a peptide‐based coating can prevent the adhesion of Porphyromonas gingivalis, a key human pathogen associated with periodontitis and peri‐implantitis. Background: Nonsurgical and surgical interventions have been used for the treatment of peri‐implantitis; however, the effectiveness of these approaches is usually unsatisfactory. The main reason is that dental plaque on the surface of the implant is difficult to remove due to its rough surface and thread design. Recently, a peptide‐based coating for implant surfaces that can reject the adhesion of Escherichia coli and improve the attachment of host cells was developed. Methods: A salivary pellicle was created on the surfaces of peptide‐coated bare discs and verified with anti‐human immunoglobulin G, A and M, and anti‐fibrinogen. Early colonizers, Veillonella parvula and Streptococcus sobrinus, and the later colonizer, Porphyromonas gingivalis, were labelled with green and red fluorescent dyes, respectively, and seeded on the discs. Bacterial attachment was semi‐quantified by fluorescence intensity. Results: The salivary pellicle was evenly distributed on the discs, with or without the peptide coating, with an average thickness of 3.84 µm. A multi‐species dental biofilm was created on the salivary pellicle. The peptide coating resulted in an approximate 25% reduction in the attachment of Veillonella parvula and Streptococcus sobrinus, and a 50% reduction in Porphyromonas gingivalis, when compared to control, uncoated implant discs. Conclusion: The novel peptide‐based coating can inhibit the attachment of Porphyromonas gingivalis . It may have the potential to impede the development of peri‐implantitis.